Molecular insights into antibody-mediated protection against the prototypic simian immunodeficiency virus - Fangzhu Zhao; Zachary T. Berndsen; Nuria Pedreño-Lopez; Alison Burns; Joel D. Allen; Shawn Barman; Wen-Hsin Lee; Srirupa Chakraborty; Sandrasegaram Gnanakaran; Leigh M. Sewall; Gabriel Ozorowski; Oliver Limbo; et al. (Nature Communications, 2022)
SIVmac239 infection of macaques is a favored model of human HIV infection, but antibody-mediated protection for SIVmac239 is insufficiently understood. Here, Zhao and Berndsen et al isolated nAbs and confirmed protection against SIVmac239 infection in passive transfer studies in macaques. The nAb was used to provide the first high-resolution structure of a rhesus SIV trimer by CryoEM. Analysis of the glycosylation pattern of this SIV trimer suggests a denser glycan shield on Env for rhesus SIV compared to chimpanzee SIV or HIV-1, which partially explains the poor nAb response of rhesus macaques to SIVmac239 infection.